1998
DOI: 10.1002/(sici)1096-9861(19981102)400:4<529::aid-cne7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Cellular terrain surrounding sympathetic nerve pathways in the rat orbit: Comparisons of orbital connective tissue and smooth muscle cell phenotypes

Abstract: Sympathetic axons are abundant within some orbital tissues but are absent from others. This study investigated cellular phenotypes of tissues containing sympathetic nerves en passage and compared these with phenotypes in regions devoid of sympathetic nerves and with smooth muscle targets. Two primary orbital smooth muscle targets, the tarsal muscle and orbital muscle, contained many synaptophysin-immunoreactive nerves. Target cells had ultrastructural features typical of smooth muscle and were immunoreactive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Together, the spatial and temporal associations observed suggest that myofibroblasts may possess neurotrophic properties. In some normal tissues, nerves are frequently associated with myofibroblast-like cells (Nistal et al 1982;Saito 1990;Tamm et al 1995;Smith et al 1998), leading us to propose a neurotrophic role for these cells. Wound myofibroblasts may also regulate innervation, as they can produce extracellular matrix factors such as laminin that are known to promote neurite outgrowth (Eddy et al 1988;Berndt et al 1994), and may synthesize nerve growth factor ( Matsuda et al 1998;Hasan et al 1998), thus contributing to the high levels of this neurotrophin at the wound site (Constantinou et al 1994).…”
Section: Myofibroblasts As Neurotrophic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, the spatial and temporal associations observed suggest that myofibroblasts may possess neurotrophic properties. In some normal tissues, nerves are frequently associated with myofibroblast-like cells (Nistal et al 1982;Saito 1990;Tamm et al 1995;Smith et al 1998), leading us to propose a neurotrophic role for these cells. Wound myofibroblasts may also regulate innervation, as they can produce extracellular matrix factors such as laminin that are known to promote neurite outgrowth (Eddy et al 1988;Berndt et al 1994), and may synthesize nerve growth factor ( Matsuda et al 1998;Hasan et al 1998), thus contributing to the high levels of this neurotrophin at the wound site (Constantinou et al 1994).…”
Section: Myofibroblasts As Neurotrophic Cellsmentioning
confidence: 99%
“…Myofibroblasts appear with the formation of granulation tissue in the early phase of wound closure, and disappear in the later stages, presumably as a result of apoptosis (Desmouliere et al 1997). While associations between wound myofibroblasts and regenerating nerves apparently have not been investigated, cells with myofibroblast features are present in some normal tissues, where they are frequently associated with nerves (Nistal et al 1982;Tamm et al 1995;Smith et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 50% arise from local resident fibroblasts via proliferation, 35% are derived via differentiation from bone marrow, 10% result from endothelial-to-mesenchymal transition (EndMT), and 5% originate from epithelial-to-mesenchymal transition (EMT) [ 6 ]. Apart from those above, cells of the synthetic phenotype of SMCs, which are derived from the contractile SMC phenotype, can reflect both fibroblast and smooth muscle features, similar to myofibroblasts [ 7 ] and also participate in renal progressive vascular sclerosis and fibrosis [ 8 , 9 ] by producing excessive matrix elements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fibronectin has been shown to have potent effects on sympathetic nerve outgrowth and vessel innervation (26,27). Cunha e Sa et al (28) demonstrated that malformed cortical vessels in SWS are innervated only by noradrenergic sympathetic nerve fibers.…”
mentioning
confidence: 99%